Building sustainability through environmental education - Wilson, Lynn A., 1954-; Stevenson, Carolyn, 1968- (Engineering Science Reference, 2019)
"This book stems the rising tide of shortcomings in environmental education by plugging a known gap in current research and opening a dialogue for the future. This volume provides a much needed dam of empirical evidence regarding the role of youth education in addressing one of the greatest challenges of our age"--